Writing to the king. The correspondence from Sardinia at the time of Alfonso the Magnanimous (1416-1419) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
The present essay aims at analyzing the formal characteristics of the correspondence produced in Sardinia addressed to the King of Aragon by various officials, members of the city authorities, nobles and others who stayed on the island during the first years of the reign of Alfonso the Magnanimous. These testimonies are nowadays preserved in the Cartas Reales series of the Archive of the Crown of Aragon. Through the analysis of the intrinsic and extrinsic characteristics of the letters, the production model of 15th-century Sardinian letters is proposed, highlighting their peculiarities and characteristics.
Keywords: Sardinia; Diplomatics; Correspondence; Alfonso the Magnanimous